Multi-dimensional indices to stage idiopathic pulmonary fibrosis: a systematic review - Rozanski, Camilla; Mura, Marco (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Idiopathic pulmonary fibrosis (IPF) has the highest mortality rate among all interstitial lung diseases, with a mean survival time of 2 to 3 years from the time of diagnosis. Prognosis is difficult to determine, due to the recognized heterogeneous progression of the disease, as well as lack of a well recognized staging system. This in turn raises challenges when considering therapeutic options for IPF patients, such as lung transplantation, versus a more conservative approach.  Multiple independent factors have been identified as prognostic indicators in IPF, and a number of studies have proposed multi-dimensional indices that combine several parameters in order to achieve a more accurate delineation of disease progression. In this systematic review, the Pubmed database was used to identify studies in the area of multi-dimensional staging of IPF.  We analysed and critically appraised previously proposed prognostic scoring systems. Our aim is to encourage research developments in this area to help identify an optimal multi-dimensional staging system for IPF.